PROBLEMATICS OF HOUSEHOLD LIFE PAIR OF HUSBAND-WIFE FAMILY LAW ISLAMIC PERSPECTIVE - Musaitir Musaitir (Universitas Islam Negeri (UIN) Mataram, 2020)
A household problem is a problematic situation, the mismatch between husband and wife partners, causing conflicts, disputes, and disputes between the two. Life in marriage will also always experience changes and ups and downs, this is what is called the dynamics of marriage. Many things will affect the dynamics of this marriage, some marriages turn out to be harmonious because husband and wife are not ready to play their role in marriage. Problems that occur in the household, for married couples, not only cause household life to be disharmonious but can lead to divorce. Domestic problems occur, both in young and adult married couples, with various types of problems faced by each married couple in living their domestic life.